IT Protection of Safety-Related Machine Control Systems in Industry 4.0 - Marek DŹWIAREK (Ochrona informatyczna związanych z bezpieczeństwem systemów sterowania maszynami w Przemyśle 4.0, 2022)
The overall objective of the research was to develop the consideration of threats of unauthorized interference in information systems in the risk assessment process carried out by designers of machine control systems. For this purpose, an analysis of typical structures related to the security of control systems was carried out in terms of the possibility and consequences of the loss of security functions as a result of unwanted interference. Recommendations for proceeding “step by step” in the subsequent stages of the risk analysis were determined.
Keywords: Ochrona informatyczna systemów sterowania maszynami